GEOLOGY OF PART OF BENTA IGNEOUS COMPLEX WITH EMPHASIS ON PETROLOGY AND FRACTURE ANALYSIS - BIN ROSI, ABDUL MUIZ (Universiti Teknologi PETRONAS, 2015)
Transect along Benta area located in the range of Central Belt igneous complex structure. The Central Belt is shown to be separated from its margin by northerly fault zones. The faults are justifies as normal fault that related to the continental rifting and graben formation during late Paleozoic to Mesozoic age. It is determined that the Benta igneous complex are in the Jurassic age. The Benta formation is related to the magmatism beneath the Central Belt that due to mantle plum processes. It is associated with post orogenic processes and does not associated with the oceanic crust subduction as it would have been ended by Latest Permian-Triassic collision. The Benta complex rocks are shoshonitic, which would occur furthers away from a trench, but found closely to the Bentong-Raub Line. Previous studied done by Mohd Rozi (2000) indicates that Benta area, especially near Jeram Besu are rich in quartz diorite, porphyry syenite and monzonite.